Cutaneous side effects of molecularly targeted therapies for the treatment of solid tumors - Daniel I G Cubero; Beatrice Martinez Zugaib Abdalla; Jean Schoueri; Fabio Iazetti Lopes; Karine Corcione Turke; Jose Guzman; Auro Del Giglio; Carlos D'Apparecida Santos Machado Filho; Vanessa Salzano; Dolores Gonzalez Fabra (BioExcel Publishing Ltd, 2018)
Background: Currently, molecularly targeted drugs are part of the therapeutic arsenal for the treatment of many neoplasms and are responsible for improvements in the quality of life and survival of patients. Although they act on proteins and components within biochemical pathways that are expressed to a greater extent in neoplastic cells, these drugs can also interfere with the activity of normal cells. Scope: This article reviews the cutaneous side effects of main molecularly targeted cancer therapies for solid tumors. Findings: The use of these drugs causes side effects, and the skin is one of the most commonly affected organs. In this literature review, we discuss the adverse cutaneous effects caused by molecularly targeted drugs. Conclusion: The identification of these reactions is important to both dermatologists and oncologists so that they properly diagnose the reaction and administer adequate treatment, which would allow greater adherence to the oncological treatment and improve patients' quality of life.